1995
DOI: 10.1051/apido:19950101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diflubenzuron and penfluron on workers of Apis cerana indica F and Apis mellifera L

Abstract: Summary — Newly emerged adult workers of Apis mellifera and A cerana indica tolerated a topically applied dose of 100 μg diflubenzuron (DF) and penfluron (PF) in acetone but the treated bees weighed less than control bees at 2 and 6 d of age. Oral administration of 100 μg DF (as Dimilin 25% wettable powder) in 10 μl sugar syrup proved fatal to A c indica. After 6 d of feeding 50 μg DF, hypopharyngeal gland development, measured as size of acini, was significantly suppressed in both bee specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
(14 reference statements)
0
18
0
1
Order By: Relevance
“…De ce fait, ils risquent peu de produire des dommages chez les adultes, par contre ils peuvent engendrer des troubles dans le couvain. L'application d'analogues d'hormones à des abeilles adultes a modifié le comportement de butinage, la production de phéromone d'alarme, l'hémolymphe, le gain de poids, la synthèse de la vitellogénine, la longévité et a inhibé les glandes hypopharyngiennes (Redfern et Knox, 1974 ;Jaycox et al, 1974 ;Rutz et al, 1974 ;Gerig, 1975 ;Atkins et al, 1976 ;Robinson, 1985 ;Usha et Kadasamy, 1986 ;Ceparano et Job, 1989 ;Gupta et Chandel, 1995 ;Pinto et al, 2000). Chez les larves l'intoxication expérimentale par contact ou par ingestion provoque la mort des oeufs, des larves, ou des malformations des larves, des nymphes ou des adultes.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…De ce fait, ils risquent peu de produire des dommages chez les adultes, par contre ils peuvent engendrer des troubles dans le couvain. L'application d'analogues d'hormones à des abeilles adultes a modifié le comportement de butinage, la production de phéromone d'alarme, l'hémolymphe, le gain de poids, la synthèse de la vitellogénine, la longévité et a inhibé les glandes hypopharyngiennes (Redfern et Knox, 1974 ;Jaycox et al, 1974 ;Rutz et al, 1974 ;Gerig, 1975 ;Atkins et al, 1976 ;Robinson, 1985 ;Usha et Kadasamy, 1986 ;Ceparano et Job, 1989 ;Gupta et Chandel, 1995 ;Pinto et al, 2000). Chez les larves l'intoxication expérimentale par contact ou par ingestion provoque la mort des oeufs, des larves, ou des malformations des larves, des nymphes ou des adultes.…”
Section: Resultsunclassified
“…kg -1 the authors concluded that this chitin synthesis inhibitor was the safest and should be recommended for integrated pest management. Diflubenzuron was also tested on newly emerged adults of A. mellifera and A. cerana indica by Gupta and Chandel (1995). They found that topical applications of 100 µg doses were tolerated by treated bees but resulted in a reduced weight gain.…”
Section: Symptoms Of Igr Intoxication In Adultsmentioning
confidence: 99%
“…Hypopharyngeal glandular development should be assessed in newly-emerged bees after 10 days of exposure. Head weight has been directly correlated to the development and size of hypopharyngeal glands (Hrassnigg and Crailsheim, 1998;Babendreier et al, 2005) and used to test the effect of pesticides (Gupta and Chandel, 1995). Although not reported here, preliminary data on head weight indicated that a large sample size would be required due to the high variance and small changes in head weight that could indicate an adverse effect.…”
Section: Laboratory Studiesmentioning
confidence: 87%
“…For this reason, gland size and acini diameter have been used as indicators to test the effect of various food sources such as pollen from different plants (Standifer, 1967) or pesticides (Gupta and Chandel, 1995). As protein turnover is high in the hypopharyngeal glands, we hypothesized that feeding on transgenic protein may influence the development of these glands in young nurse bees.…”
Section: Babendreier Et Almentioning
confidence: 99%